Electrodeposited CdTe solar cells using low-purity Cd precursors & the effect of chemical purity - Ashfaque E. Alam; Hussain I. Salim; Ayotunde A. Ojo; Imyhamy M. Dharmadasa (Academia Materials Science)
Electrodeposited cadmium telluride (CdTe) solar cells are conventionally fabricated with high-purity (≥99%) cadmium precursors. The current record efficiency of 15.3% was achieved from 99.997% pure cadmium nitrate precursors. This work aims to test the utility of lower-cost, lower-purity precursors and compare the performances as a function of the precursor purity. Initially, CdTe thin films were electroplated from an electrolyte containing 98% pure cadmium nitrate tetrahydrate and tellurium dioxide in an acidic aqueous medium. Glass/fluorine-doped tin oxide (FTO) substrates have been used to electrodeposit the semiconductor layers. The as-deposited (AD) layers were heat-treated in the air with CdCl2. The structural, compositional, electrical, optical, and morphological characterizations of the CdTe thin films were studied, and the optimal growth voltage for achieving stoichiometric CdTe has been identified. The optimized layers have been used in fabricating thin-film solar cells having glass/FTO/n-CdS/n-CdTe/p-CdTe/Au architecture, which currently holds the record efficiency. The solar cells have been investigated with illuminated current-voltage analysis. A comprehensive comparison with the previous works carried out with higher-purity chemicals has been performed for both the material properties and device parameters achieved using low-purity Cd precursors. The optimal growth voltage for CdTe with low-purity precursors was found to be 1,315 mV and a ~6.0% device efficiency was achieved. It has been observed that the use of very high-purity precursors can ensure considerably higher performance; however, it is possible to play an important role in the performance versus cost trade-off using low-purity chemicals too.